Exploring Teachers’ Lived Experiences on the Integration of Values Education in South African High Schools - Joseph Lamlani Khathi; Oluwatoyin Ayodele Ajani; Samantha Govender (Research in Social Sciences and Technology, 2022)
Values education has become a necessary tool in response to the rise in moral deterioration in an average South African society today. The school is viewed as one of the key players in nurturing children into adulthood. The teaching of values that can give the growing generation, necessary moral development is one of the responsibilities of the schools. Hence, this study aims at exploring teachers’ experiences on how they integrate values education into South African learners in various high schools. This qualitative study engaged five schools in its case study, where five teachers from each of the schools were purposively selected for semi-structured focus group interviews, to share their experiences on the integration of moral values in schools. Moral development theory was used to underpin the study. Findings from the inductive thematic analysis from the participants from both rural and urban schools indicated a misunderstanding of the concept of values education by some teachers, which affects its effective integration. The study established that role modelling of learners by teachers and parents are inevitable to save the society from moral decadence, while some participants indicted overpopulation, single parenthood, social media as some of the challenges to the integration of value education in schools. The study, therefore, recommends capacitation of teachers through various professional development programmes, to integrate values education and adequate parental support as some of the strategies to promote effective integration of values education in schools.